Participation of electrolytic aluminum loads in grid interaction control strategies considering process flow and regulation costs - Wang, Xi; Chen, Baorui; Xie, Haocong; Ye, Xi; Bai, Jiayu (Frontiers in Energy Research, 2025)
The flexibility of power systems needs to be enhanced to address the volatility of renewable energy sources, and industrial loads on the demand side have significant potential to improve this flexibility. As a typical high-energy-consuming industrial load, electrolytic aluminum has advantages such as large individual capacity and strong power controllability. However, its participation in various types of grid interaction faces challenges such as unclear power control methods, impacts on normal production, and associated cost burdens. To address these issues, this paper analyzes the production process characteristics of electrolytic aluminum loads and establishes a power control model for these loads. It examines the effects of power regulation on normal production, explores the mechanisms behind regulation costs, and proposes a method for calculating these costs. Considering production safety constraints and power regulation constraints during grid interaction, the paper proposes a control strategy for electrolytic aluminum loads that incorporates process flow and regulation costs. In the case study, the above power control strategy is verified based on the production data of an electrolytic aluminum load. The results show that the above strategy can take into account the response requirements of the power grid and the safety requirements of the load production. A feasible scheme is proposed for the electrolytic aluminum industrial load to participate in the interactive control of the power grid.